2012
DOI: 10.1523/jneurosci.3860-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-21 Regulates Astrocytic Response Following Spinal Cord Injury

Abstract: Astrogliosis following spinal cord injury (SCI) involves an early hypertrophic response that serves to repair damaged blood brain barrier and a subsequent hyperplastic response that results in a dense scar that impedes axon regeneration. The mechanisms regulating these two phases of astrogliosis are beginning to be elucidated. In this study, we found that microRNA-21 (miR-21) increases in a time-dependent manner following SCI in mouse. Astrocytes adjacent to the lesion area express high levels of miR-21 wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(172 citation statements)
references
References 53 publications
(82 reference statements)
6
166
0
Order By: Relevance
“…These results indicate a specific role of BMPRIA in the initial injury response; however, Bmpr1a 2/2 mice show better recovery 5 weeks postinjury, suggesting that BMPRIB regulates glial scar progression (Sahni et al 2010). Further, miR-21, a posttranscriptional regulator of gene expression induced by BMP signaling, mediates the astrocytic response after spinal cord injury (Sahni et al 2010;Bhalala et al 2012). Thus, many members of the TGF-b family have important roles following CNS injury, although these processes have yet to be fully understood.…”
Section: Injury and Repairmentioning
confidence: 99%
“…These results indicate a specific role of BMPRIA in the initial injury response; however, Bmpr1a 2/2 mice show better recovery 5 weeks postinjury, suggesting that BMPRIB regulates glial scar progression (Sahni et al 2010). Further, miR-21, a posttranscriptional regulator of gene expression induced by BMP signaling, mediates the astrocytic response after spinal cord injury (Sahni et al 2010;Bhalala et al 2012). Thus, many members of the TGF-b family have important roles following CNS injury, although these processes have yet to be fully understood.…”
Section: Injury and Repairmentioning
confidence: 99%
“…reported that miR-21 regulates astrocytic hypertrophy and glial scar progression after SCi, which implicates epigenetic regulation as a potential therapeutic target for manipulating glial scar formation and improving functional performance [82] .…”
Section: Signal Transducer and Activator Of Transcription And Interlementioning
confidence: 99%
“…in addition, a study of PKC disruption by the inhibitor Gö6976 has linked an increase in the regeneration of dorsal column axons with the inactivation of CSPGs after dorsal spinal cord hemisection [81] . More interestingly, Bhalala et al recentlyreported that miR-21 regulates astrocytic hypertrophy and glial scar progression after SCi, which implicates epigenetic regulation as a potential therapeutic target for manipulating glial scar formation and improving functional performance [82] . …”
mentioning
confidence: 99%
“…While both miRs are increased in spinal cord after spinal cord injury, the second also increases in the prefontal cortex of the brain in a model of carrageenan induced facial inflammatory pain. Importantly the increase of miR-223 coincides with the peak of mechanical hyperalgesia, suggesting a role of this miR in the process [94][95][96]. Regarding deregulation of miR-21 and its connexion to pain mechanisms we should point out that Simeoli (EVs), including exosomes, loaded with miR-21 upon capsaicin activation of TRPV1 receptors.…”
Section: Mt Impact On the Nervous System And On Pain Reliefmentioning
confidence: 98%